Exploring extreme rainfall events in KwaZulu-Natal over the period 1989-2019 - Ntleko, Thabisile Phiwengomusa Zibusisozonke (My University, 2024)
Changes in weather and climate extremes have been observed across the globe. These include an increase in the frequency, magnitude, and severity of extreme events, have been attributed mainly to climate change due to increased anthropogenic activity since pre-industrial times. Although these weather and extreme events have increased and intensified globally on average, some spatial and temporal variations of trends are evident at regional scales. This study was conducted to explore the incidence and trends of extreme rainfall events over KwaZulu-Natal for the period 1989-2019. Rainfall data was sourced from the South African Weather Service for 11 stations distributed across the province. Extreme climate events (ECEs) were identified by calculating subsets of the World Meteorological Organisation (WMO) Expert Team on Climate Change Detection Indices (ETCCDI) and WMO Expert on Sector-Specific Climate Indices (ET-SCI) for each of the 30 years of interest. Thereafter, trends in these extreme climate events were calculated using linear regression. The results reveal marked spatial and temporal differences in both the occurrence of the ECEs and their trends. The incidence of ECEs depict a seasonal pattern, where majority of events occur during the summer rainfall months. However, over the coastal regions ECE’s occur throughout the year and exhibit more frequent and intense events compared to overland regions. The trend analysis detected a majority of decreasing trends in the frequency, intensity and duration of extreme rainfall events for the period of study, with only 10 of the 77 calculated trends being statistically significant. The spatial distribution of trends was heterogeneous for most parts of the province apart for the KwaZulu-Natal Midlands, which consistently observed decreasing trends for all calculated indices.
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Geography Archaeology and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Extreme rainfall events; Climate change; KwaZulu-Natal